Premarital HIV testing in Malaysia: a qualitative exploratory study on the views of major stakeholders involved in HIV prevention - Sima Barmania; Syed Mohamed Aljunid (BMC, 2017)
Abstract Background HIV screening has existed in numerous methods as an important part of HIV prevention efforts over the years. Premarital HIV testing for couples who wish to marry has been implemented in a number of regions, which often operate in a mandatory rather than voluntary basis and is considered a contentious issue, with viewpoints held in favour and against. One such region is Malaysia which has a policy of mandatory premarital HIV testing of prospective Muslim married couples. The purpose of this study is to understand stakeholders' views on premarital HIV testing given the Malaysian Islamic context. Methods 35 in-depth face to face semi-structured interviews were undertaken with key stakeholder groups involved in HIV prevention policy in Malaysia, namely, officials from the Ministry of Health, religious leaders and people living with HIV. Participants were recruited from the Klang Valley area, from July to December 2013, using purposive sampling techniques. Inclusion criteria necessitated that participants were over the age of 18 and provided full consent. Interviews were audiotaped, followed a standardised topic guide, transcribed verbatim and analysed using a framework analysis. Results Participants identified pre-marital HIV testing as an effective HIV prevention policy implemented in Malaysia and was viewed, for the most part, as a positive initiative across all stakeholders. Religious leaders were supportive of testing as it provides a protective mechanism, in line with the teachings of the Shariah, while Ministry of Health officials considered it a normal part of their HIV prevention screening initiatives. However, there were concerns surrounding issues such as confidentiality, counselling and discrimination surrounding the test described by the PLHIV group. Conclusion The findings of this study show that among the participants interviewed was strong support for mandatory premarital HIV testing, which could possibly expose the vulnerability to HIV, reluctance to test and other areas in the HIV response in Malaysia that need to be addressed. Furthermore, although international health organisations are vehemently against mandatory premarital HIV testing, the strong local support for such measures and the mismatch between these views is worth exploring in more detail, given the cultural, social and religious context.